2008
DOI: 10.1007/s11192-007-1970-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the scientific quality achieved by funding instruments for single grant holders and for collaborative networks within a research system: Some observations

Abstract: The working papers are produced by The University of Manchester -Manchester Business School and are to be circulated for discussion purposes only. Their contents should be considered to be preliminary. The papers are expected to be published in due course, in a revised form and should not be quoted without the authors' permission. Author(s) and affiliation AbstractIncreasingly, funding of academic research is carried out through the support of collaboration, rather than through single awards to a sole grant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…These results support the observations of Katz and Hicks (1997) and Rigby (2009) that international collaborations tend to produce more highly cited papers than do collaborations of people in a single country. It is interesting to note that despite the regional collaborations involving more authors and one or more ASEAN countries, the citation count was lower compared to that for single-author publications or publications that did not involve collaborations (Fig.…”
Section: Collaborationsupporting
confidence: 88%
“…These results support the observations of Katz and Hicks (1997) and Rigby (2009) that international collaborations tend to produce more highly cited papers than do collaborations of people in a single country. It is interesting to note that despite the regional collaborations involving more authors and one or more ASEAN countries, the citation count was lower compared to that for single-author publications or publications that did not involve collaborations (Fig.…”
Section: Collaborationsupporting
confidence: 88%
“…Similarly, Defazio, Lockett and Wright (2009) found that while funding increased researcher productivity by approximately 14%, collaboration increased it by almost 70%. The positive effect of collaboration on the scientific impact of papers has also been shown using citations analysis (Beaver, 2004;Katz and Hicks, 1997;Larivière, Gingras, Sugimoto and Tsou, 2015;Levitt and Thelwall, 2010;Rigby, 2009). Finally, Sun, Kaur, Milojević, Flammini and Menczer (2013) found that scientific disciplines emerge from the splitting and merging of social communities in a collaboration network, which supports the theory that scientific collaboration shapes the dynamics of science.…”
Section: Economic and Scientific Growthsupporting
confidence: 55%
“…Cimenler et al (2014) summarized that scientific collaboration provide several salient advantages: (1) "access to expertise for complex problems, new resources and, funding" (Beaver, 2001;Board, 2012;Bukvova, 2010;Hale, 2012;Hara et al, 2003;Katz & Martin, 1997;Melin, 2000;Sonnenwald, 2007), (2) "increase in the participants' visibility and recognition" (Beaver, 2001;Katz & Martin, 1997), (3) "rapid solutions for more encompassing problems by creating a synergetic effect among participants" (Beaver, 2001;Melin & Persson, 1996), (4) "decrease in the risks and possible errors made, thereby increasing accuracy of research and quality of results due to multiple viewpoints" (Beaver, 2001;Bukvova, 2010), (5) "growth in advancement of scientific disciplines and cross-fertilization across scientific disciplines" (Beaver, 2001;Cummings & Kiesler, 2005), (6) "development of the scientific knowledge and technical human capital, e.g., participants' formal education and training, and their social relations and network ties with other scientists" (Bozeman & Corley, 2004), and (7) "increase in the scientific productivity of individuals and their career growth" (Bozeman & Corley, 2004;Fox, 1983;Katz & Martin, 1997;Lee & Bozeman, 2005). Furthermore, the social dimension of scientific work; such as informal conversational exchanges between colleagues (Bozeman & Corley, 2004;Katz & Martin, 1997), co-authorship relations (Glänzel & Schubert, 2004;Katz & Martin, 1997), jointly submitted grant proposals (Katz & Martin, 1997;Rigby, 2009), and co-patent applications (Balconi, Breschi, & Lissoni, 2004;Meyer & Bhattacharya, 2004) is an important leading factor which leads to the above mentioned advantages of scientific collaboration …”
Section: Scientific Collaborationmentioning
confidence: 99%